The Influence of Brand Image, Price Discounts, and Bonus Packs on Impulse Buying Behavior among Indomaret Point Coffee Consumers Mojokerto City - Octafehili, Dwi Nur; Sari, Dewi Komala; Yulianto, Mochamad Rizal (Universitas Alma Ata, 2024)
This research aims to determine the influence of brand image, price discounts, and bonus packs on impulse buying behavior among consumers at Indomaret Point Coffee in Mojokerto City. The significance of this research lies in its effort to provide deep insights into the factors influencing consumers' impulsive behavior, which can be used by companies to develop more effective marketing strategies. The research problem focuses on understanding how factors such as brand image, price discounts, and bonus packs can affect impulsive purchasing decisions among consumers. This is important because consumers' impulsive behavior can impact revenue and customer loyalty toward a brand or product. The method used in this study is quantitative with a descriptive analysis approach. The population of this study comprises consumers of Indomaret Point Coffee in Mojokerto City. The sampling technique used is non-probability sampling with a purposive sampling method, meaning respondents are selected based on certain criteria, namely consumers who have purchased products at Indomaret Point Coffee. Data collection was carried out by distributing questionnaires, where responses were measured using a Likert scale. Data analysis was conducted using multiple linear regression tests through the Statistical Package for the Social Sciences (SPSS) software version 25. The findings of the study show that the three variables, namely brand image, price discount, and bonus pack, have a significant influence on the impulse buying behavior of consumers at Indomaret Point Coffee in Mojokerto City. Brand image has been proven to have a positive influence on impulsive buying behavior, as do price discounts and bonus packs, each showing a positive relationship with consumers' impulsive behavior. These results indicate that to increase sales through impulsive buying behavior, Indomaret Point Coffee needs to pay attention to and optimize these three factors in its marketing strategy.